Analisis Strategi Pemasaran Syariah Produk Elzatta - Muhammad Fikri; Rofiqoh Ferawati; Mohammad Orinaldi (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This research was carried out based on data saying that Elzatta in the period from year to year experienced an increase in percentage as the brand with the best quality, it's just that in 2019 it experienced a slight decrease in numbers, this might have been due to the Covid-19 pandemic that hit the Indonesian nation at that time and of course slightly affected the brand process at Elzatta. Thus, based on the results of the initial observations and analysis above, which found a uniqueness in Elzatta using a sharia marketing strategy for their products, the researcher was compelled to describe this phenomenon, namely related to the Islamic marketing strategy implemented by the Elzatta store so that it continues to exist in the face of real world business competition This research uses a type of qualitative research by using data collection methods in the form of observations, interviews, and documentation. The technique of analyzing the data is by filtering the data, presenting the data, and cross-checking the data. While testing the validity of the data is done using triangulation techniques. The results of this study found that: 1. Elzatta's product sharia marketing strategy was carried out with three main strategies, namely: (1) Market segmentation; (2) Targeting and Positioning; and (3) combination strategy which includes: strategy in maintaining the product; price range strategy; strategy in choosing a point of sale; strategy in the field of product promotion; strategy in HR management; strategy in the easy shopping process; strategy in the marketing process through social media. 2. Supporting factors for the sharia marketing strategy for Elzatta products are due to several factors, namely: Maintaining service quality; Understanding customer needs and company needs through SWOT analysis; Neat employee appearance; Responsiveness in helping customers online/offline; Providing supplies/training to employees/SPG; Sensitivity to the development of global business competition. 3. The inhibiting factors for Elzatta's sharia marketing strategy are internal and external factors. Internal reasons, including: capital, promotion constraints in the field. Meanwhile, these external factors include: price competition and the promotion strategy of Elzatta Jambi's competitors.